Urolithin B: Two-way attack on IAPP proteotoxicity with implications for diabetes - Raimundo, Ana F.; Ferreira, Sofia; Pobre, Vânia; Lopes-da-Silva, Mafalda; Brito, José A.; dos Santos, Daniel J. V. A.; Saraiva, Nuno; dos Santos, Cláudia N.; Menezes, Regina (Frontiers in Endocrinology, 2022)
Introduction Diabetes is one of the major metabolic diseases worldwide. Despite being a complex systemic pathology, the aggregation and deposition of Islet Amyloid Polypeptide (IAPP), or amylin, is a recognized histopathological marker of the disease. Although IAPP proteotoxicity represents an important trigger of β-cell dysfunction and ultimately death, its exploitation as a therapeutic tool remains underdeveloped. The bioactivity of (poly)phenols towards inhibition of pathological protein aggregation is well known, however, most of the identified molecules have limited bioavailability. Methods Using a strategy combining in silico, cell-free and cell studies, we scrutinized a unique in-house collection of (poly)phenol metabolites predicted to appear in the human circulation after (poly)phenols ingestion. Results We identified urolithin B as a potent inhibitor of IAPP aggregation and a powerful modulator of cell homeostasis pathways. Urolithin B was shown to affect IAPP aggregation pattern, delaying the formation of amyloid fibrils and altering their size and morphology. The molecular mechanisms underlying urolithin B-mediated protection include protein clearance pathways, mitochondrial function, and cell cycle ultimately rescuing IAPP-mediated cell dysfunction and death. Discussion In brief, our study uncovered urolithin B as a novel small molecule targeting IAPP pathological aggregation with potential to be exploited as a therapeutic tool for mitigating cellular dysfunction in diabetes. Resulting from the colonic metabolism of dietary ellagic acid in the human body, urolithin B bioactivity has the potential to be explored in nutritional, nutraceutical, and pharmacological perspectives.